Lecturer Autoethnographies of Adjusting to Online Student Interactions during COVID-19 - Sandra Makwembere; Obert Matarirano; Nobert Rangarirai Jere (Research in Social Sciences and Technology, 2021)
In 2020, the COVID-19 pandemic pushed South African historically disadvantaged institutions, that had not yet reached advanced levels of technology use in teaching and learning, to find immediate solutions to salvage the disrupted academic year. Interactions with students, which had predominantly been face-to-face, shifted to various online platforms for lecturers to adopt emergency remote teaching approaches. Most of the lecturers were unprepared or incapacitated to make the shift to online environment. Studies have looked at the online teaching and learning experiences of students and lecturers during the COVID-19 pandemic but very few have taken an autoethographic approach to their inquiry and situated experiences in historically disadvantaged institutions. In this article, as lecturers, we use autoethnographies to provide an account of adjusting to interacting with students online during national lockdowns at a historically disadvantaged institution. The Social Cognitive Theory (SCT) was applied to guide the study. This reflexive approach is valuable, as it captures professional encounters and reflections needed to understand the effects of rapid changes to teaching and learning in response to the pandemic. Given the education disparities that already existed between South African higher education institutions before COVID-19, the article contributes to the discourse on how historically disadvantaged institutions can advance higher standards of teaching and learning to serve students better. Our reflections point to the personal, technical and structural challenges of maintaining regular online interaction. Our findings show that different approaches and techniques were applied to adjust to virtual teaching and learning. As teaching and learning methodologies have the potential to ingrain social inequalities, we made recommendations on how to improve online interactions with students from historically disadvantaged contexts.